Preparation method and preparation process of BMC plastic

Through the molding process and the synthesis of polyurethane prepolymers, combined with hollow ceramic microbeads and tert-butyl ester, the high density and brittleness of BMC materials are solved, and its toughness and insulation performance are improved, density reduction and performance improvement are achieved. Energy conservation, emission reduction and cost reduction demand.

CN119320547AInactive Publication Date: 2025-01-17YUEQING ZHONGSHENG PLASTIC CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411857370.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the high density double bonds of unsaturated polyester, the degree of crosslinking after curing is extremely high, and there are problems such as high brittleness and the product is prone to warping, cracking and deformation during shrinkage, which hinders its wide application in other fields. .

Method used

By using the molding process, by synthesizing polyurethane prepolymers and introducing hollow ceramic microbeads, the density of BMC plastics is reduced, the insulation is increased, and the mechanical properties are maintained. IPDI and hollow ceramic microbeads are used to form polyurethane prepolymers, and tert-dit Esters are used as curing agents to improve cross-linking density and hardness.

Benefits of technology

It effectively reduces the density of BMC plastic, improves its toughness and insulation properties, ensures product quality while reducing production costs, helps energy conservation and emission reduction, and improves the wear and corrosion resistance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320547A_ABST
    Figure CN119320547A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and a preparation process of BMC (bulk molding compound) plastic, and relates to the technical field of polymer composites.The BMC plastic is prepared from, by weight, 60-90 parts of resin, 1-6 parts of pigment paste, 10-40 parts of polyurethane prepolymer, 8-18 parts of low shrinkage agent, 0.8-1.4 parts of physical thickening agent and 40-65 parts of glass fiber. The BMC plastic is prepared from, by weight, 3-7 parts of zinc stearate (Zn-th), 0.4-1 part of calcium hydroxide, 0.3-1 part of curing agent and 100-140 parts of kneading agent, hollow ceramic microbeads and IPDI are fused into polyurethane prepolymer, isocyanate group (-NCO) is introduced to react with double bonds in unsaturated polyester, the density of the double bonds in the unsaturated polyester is reduced, the toughness of the BMC plastic is improved, the density of the BMC plastic is reduced through the hollow ceramic microbeads, and the toughness of the BMC plastic is improved. Meanwhile, the insulating property of the BMC plastic is improved, tert-butyl ester is introduced as a curing agent, the problems that the curing time is prolonged and crosslinking points are reduced due to reduction of the density of double bonds are solved, and the material is more wear-resistant and corrosion-resistant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, and in particular to a method and process for preparing BMC plastic. Background Art

[0002] BMC (Bulk Molding Compound) material, namely bulk molding compound, is an intermediate material for unsaturated polyester composite products. The main raw materials of BMC materials include glass fiber, unsaturated polyester resin, filler and various additives required for hot pressing molding; BMC materials have excellent physical and chemical properties. With their excellent electrical insulation, heat resistance, flame retardancy and good mechanical strength, they are widely used in electronic appliances, automobile manufacturing, sanitary ware and other fields. However, since the unsaturated polyester used in BMC materials has a high density of double bonds, the degree of cross-linking after curing is extremely high. At the same time, BMC materials also have defects such as high brittleness, and the products are prone to warping, cracking and deformation during the shrinkage process. These problems seriously hinder its wide application in other fields.

[0003] The formula of BMC material is designable. By adjusting the proportion and type of each raw material in the formula and coordinating different production processes, BMC materials with different properties such as flame retardancy, wear resistance, and electrical insulation can be manufactured. Low-density BMC material is one of the important modification directions of BMC material. Generally speaking, the density of BMC molding compound is 1.7-1.9g / cm 3 , appropriately reducing its density can reduce the mass of the product, which is helpful for energy conservation and emission reduction while reducing production costs. Compared with traditional fillers such as calcium carbonate, artificial glass or silicate microspheres have lower density. Although lightweight fillers may reduce the density of the material to a certain extent, through reasonable formula design and process control, it can be ensured that BMC materials still have good mechanical properties while maintaining a low density. The addition of artificial glass or silicate microsphere fillers can also improve the processing properties of BMC materials, such as improving the fluidity and moldability of the material, which is conducive to the preparation of products with complex shapes and precise dimensions.

[0004] Polyurethane materials have excellent properties such as wear resistance, high mechanical strength, good elasticity, and aging resistance. Therefore, they are widely concerned and applied in coatings, clothing, furniture, etc. There are many ways to modify polyurethane, including acrylic modification, organic fluorine modification, organic silicon modification, nanomaterial modification, epoxy resin modification, bio-based material modification, and cross-linking modification. These methods can significantly improve the adhesion, weather resistance, water resistance, heat resistance, and mechanical properties of polyurethane. Polyurethane prepolymers contain flexible long-chain polyols, which can improve the fluidity and plasticity of the system, form a network structure to buffer the tensile energy, and effectively avoid stress concentration and local cracks. Some polyurethane prepolymers have good dispersibility in BMC and can form a tight interface layer with the glass short fibers in BMC through double bonds and hydrogen bonds, enhancing the compatibility between the fibers and the matrix. At the same time, the isocyanate group (-NCO) in the polyurethane prepolymer can react with the double bonds in the unsaturated polyester to generate new compounds containing urethane bonds. This reaction can reduce the density of double bonds in the unsaturated polyester, thereby changing its cross-linking degree and performance.

[0005] BMC molding compound molding methods mainly include compression molding, injection molding, and die-casting. Compression molding is a method of adding a certain amount of BMC premix or prepreg into a metal mold, and curing and molding it by heating and pressurizing. Injection molding is a method of pressing BMC block plastic into a plasticizing barrel through a hydraulic piston, conveying and plasticizing it under the action of the screw rotation, and injection molding. Die-casting is a molding method in which BMC molding compound is injected into a mold under high pressure, and a product is formed by cooling and curing the mold. It is mostly used for products with multiple cavities in one mold and complex and changeable structures, such as the common die-cast BMC "plastic-sealed" parts, which wrap electrical components in molding compounds to achieve the purpose of insulation, corrosion resistance, and shock resistance, and protect components from damage. Among them, compression molding has the characteristics of high production efficiency, easy to realize specialized and automated production, high product dimensional accuracy, good repeatability, the ability to mold complex products at one time, batch production, and relatively low price. It is a commonly used BMC molding compound molding method in factories. Summary of the invention

[0006] The present invention is made in view of the above problems, and its purpose is to provide a method and process for preparing BMC plastic, use a compression molding process to make a BMC plastic, synthesize a polyurethane prepolymer, introduce hollow ceramic microbeads, reduce the density of the BMC plastic, increase the insulation of the BMC plastic, and at the same time allow the BMC to still maintain strong mechanical properties, thereby ensuring product quality while reducing production costs and contributing to energy conservation and emission reduction.

[0007] The technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing BMC plastic. The raw materials include the following components by weight: 60-90 parts of resin, 1-6 parts of pigment paste, 10-40 parts of polyurethane prepolymer, 8-18 parts of low shrinkage agent, 0.8-1.4 parts of physical thickener, 40-65 parts of glass fiber, 3-7 parts of zinc stearate (Zn-ste), 0.4-1 parts of calcium hydroxide, 0.3-1 parts of curing agent, and 100-140 parts of kneading agent.

[0008] Furthermore, the pigment paste includes unsaturated polyester resin and pigment powder.

[0009] Furthermore, the polyurethane prepolymer includes IPDI and hollow ceramic microspheres.

[0010] Furthermore, the low shrinkage agent includes styrene and polystyrene.

[0011] Furthermore, the curing agent is tert-butyl ester.

[0012] Furthermore, the kneading agent is one of calcium carbonate or aluminum hydroxide.

[0013] Furthermore, the physical thickener is magnesium oxide.

[0014] Furthermore, the glass fibers are chopped glass fibers.

[0015] Furthermore, the polyurethane prepolymer is synthesized according to the following steps: (1) Prepare a solution with anhydrous ethanol and distilled water in a ratio of 8:2, add 1-5% silane coupling agent to the solution, mix well, pour into a beaker containing pre-dried hollow ceramic microbeads, place in an ultrasonic stirrer at a water temperature of 50-60 degrees Celsius, and treat for 50-60 minutes; (2) Filter out most of the filtrate from the treated hollow ceramic microbeads using a circulating water vacuum pump, and then place them in an oven to dry for 6-8 hours at a temperature of 75-90 degrees Celsius; (3) Add the measured cyclohexanone to IPDI while stirring, and then add the dried hollow ceramic microbeads in batches. After ultrasonic dispersion treatment for 30-40 minutes, pour it into a mold and solidify it under certain conditions to obtain a polyurethane prepolymer, which is then demolded and set aside.

[0016] Furthermore, the certain conditions in step (3) are curing at room temperature for 14 days and then curing at 80-120 degrees Celsius for 24 hours.

[0017] Furthermore, in the synthesis and preparation of the polyurethane prepolymer, the components of IPDI and hollow ceramic microspheres are as follows, by weight: 50-80 parts of IPDI and 20-50 parts of hollow ceramic microspheres.

[0018] In a second aspect, the present invention further provides a process for preparing BMC plastic.

[0019] The steps include: S1. Incoming inspection to ensure the quality of raw materials, maintain production order, and guarantee the final quality of products; S2. Raw material storage: Raw materials should be stored in a ventilated and dry place at room temperature; S3. Weigh, check and clean the surface of the electronic scale tray, weigh the raw materials of corresponding weight fractions, use a foam bowl to weigh polyester resin and pigment powder, use a measuring cup and a plastic box to weigh curing agent, zinc stearate, and calcium hydroxide, and clean the electronic scale and the work site after weighing; S4, pigment paste preparation, a. weigh the unsaturated polyester resin and pigment powder, place them in a bucket; b. check and clean the blades of the mixer, place the prepared pigment in the working position, put in the blades of the mixer and start stirring until the color is evenly mixed, clean the blades after stirring, and take out the barrel for use; c. check and clean the roller of the grinder, then turn on the grinder, and use a scraper fineness meter to check the fineness of the pigment paste. The scraper fineness requirement is ≤25. If it meets the standard, the grinding is completed. If it does not meet the standard, it needs to be ground again until it meets the requirements. The ground pigment paste is put into a bucket; S5. Preparation of low shrinkage agent: a. Check the mixing barrel and equipment, use a copper wrench to open the styrene barrel, and add styrene at one time according to the ratio; b. Start the propeller, add polystyrene, start the timer, and stir for 130-170 minutes, and the equipment will stop automatically; c. Put the stirred low shrinkage agent into a 14-mesh filter screen through a pipe, and then flow into the iron barrel, and lock the lid with a copper wrench; S6, kneading, a, check and clean the inside of the kneading machine; b, first add pigment paste, low shrinkage agent, curing agent, zinc stearate, calcium hydroxide, and stir for 1-2 minutes; c, turn on the kneading machine, stir for 1-2 minutes, then add calcium carbonate or aluminum hydroxide according to proportion, then close the cylinder cover, start kneading and timing; d, after stirring for 10 minutes, observe the uniformity of kneading, then start to add glass fiber evenly and slowly for multiple times, and stir for 9-16 minutes after adding; e, after self-inspection, the appearance of the material is normal, start to discharge the material and put it into an airtight film packaging bag; f, label the packaging nylon bag and inner bag; g, naturally mature the packaged BMC material at room temperature for 5 days; h, after the aging is completed, add the BMC material to the preheated mold, press and mold it, conduct quality inspection, and obtain the finished product; S7, packaging, cutting nylon ropes, arranging inner bags, and placing the packaged and tied finished products on pallets; S8, flattening, check and clean foreign objects on the work surface of the hydraulic press, set the stroke height of the hydraulic press, place the product on the work surface, and start the equipment for flattening.

[0020] Furthermore, dust masks and protective gloves must be worn throughout steps S1-S8, and fireworks are prohibited in steps S4, S5, and S6.

[0021] Furthermore, the final product is tested for relevant indicators.

[0022] The beneficial effects of the present invention are: (1) The BMC plastic prepared by the present invention is a polyurethane prepolymer prepared by fusing an organic material IPDI with an inorganic material hollow ceramic microsphere. The polyurethane prepolymer contains an isocyanate group (-NCO) which reacts with the double bonds in the unsaturated polyester to reduce the density of the double bonds in the unsaturated polyester and increase the toughness of the BMC plastic. The BMC plastic is more likely to deform and less likely to break when subjected to external force.

[0023] (2) The BMC plastic prepared by the present invention introduces hollow ceramic microspheres of inorganic materials while adding polyurethane prepolymer, thereby reducing the density of the BMC plastic and improving the insulation performance of the BMC plastic.

[0024] (3) In a BMC plastic prepared by the present invention, after adding a polyurethane prepolymer, the decrease in double bond density will lead to a prolonged curing time and a reduction in crosslinking points. The introduction of tert-butyl ester as a curing agent can rapidly react with the functional groups in the resin under appropriate conditions, thereby accelerating the curing process. This high activity ensures that the BMC material can quickly reach the desired degree of curing during the preparation process. Tert-butyl ester as a curing agent can effectively increase the crosslinking density and hardness of the BMC plastic, making the material more wear-resistant and corrosion-resistant. The combination of the curing agent and the polyurethane prepolymer greatly improves the physical and electrical properties of the BMC plastic.

[0025] (4) The BMC plastic prepared by the present invention has the best comprehensive performance when the resin is 70 parts and the polyurethane prepolymer is 30 parts. The density of the BMC plastic is significantly reduced, but the physical and electrical properties are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a process flow chart of BMC plastic preparation according to the present invention; Figure 2 It is a relationship diagram between the number of kneading agents and the water absorption rate of BMC plastic in a method for preparing BMC plastic of the present invention; Figure 3 This is a relationship diagram between the amount of curing agent and the curing time of BMC plastic in a BMC plastic preparation method of the present invention Figure 4 This is a scanning electron microscope image of a BMC plastic of the present invention at 100 microns. DETAILED DESCRIPTION

[0027] The following is a detailed description of embodiments of the present invention, but the present invention can be implemented in many different ways as defined and covered by the claims.

[0028] Example 1 A method for preparing BMC plastic, wherein the synthesis and preparation of polyurethane prepolymer, different raw material ratios and material properties under different curing conditions are shown in Table 1: Note: Curing condition A is room temperature curing for 14 days; curing condition B is room temperature curing for 14 days, then curing at 80 degrees Celsius for 24 hours; curing condition C is room temperature curing for 14 days, then curing at 100 degrees Celsius for 24 hours; curing condition D is room temperature curing for 14 days, then curing at 120 degrees Celsius for 24 hours.

[0029] The data in Table 1 show that the ratio of IPDI to hollow ceramic microspheres affects the performance of the synthesized polyurethane prepolymer. When IPDI: hollow ceramic microspheres = 60:40, the elongation at break, breaking strength and Shore hardness of the polyurethane prepolymer are better than those of other ratios. When IPDI: hollow ceramic microspheres = 70:30, the tensile strength of the polyurethane prepolymer is slightly higher than that of the polyurethane prepolymer when IPDI: hollow ceramic microspheres = 60:40. At the same time, the curing conditions also have a great influence on the performance of the synthesized polyurethane prepolymer. When the ratio of IPDI to hollow ceramic microspheres is When the example is fixed, the performance of the polyurethane prepolymer after curing at room temperature for 14 days only under curing condition A is far inferior to that of the polyurethane prepolymer cured at room temperature for 14 days and then cured at high temperature for 24 hours; under curing conditions A to D, the performance of the polyurethane prepolymer shows a trend of first rapidly increasing and then slowly decreasing, among which the polyurethane prepolymer prepared under curing condition C has the best performance. After comprehensive consideration, the polyurethane prepolymer produced by the ratio of IPDI to hollow ceramic microbeads and its curing conditions corresponding to group 7 has the best comprehensive performance. The polyurethane prepolymer synthesized in group 7 is selected as the raw material for the synthesis of BMC plastics.

[0030] Furthermore, the synthesis preparation steps of the polyurethane prepolymer are: (1) Inorganic material treatment: prepare a solution with anhydrous ethanol and distilled water in a ratio of 8:2, add 5% silane coupling agent to the solution, mix well, pour into a beaker containing pre-dried hollow ceramic microbeads, place in an ultrasonic stirrer at a water temperature of 55 degrees Celsius, and treat for 60 minutes; (2) Filter out most of the filtrate from the treated hollow ceramic microbeads using a circulating water vacuum pump, and then place them in an oven to dry for 7 hours at a temperature of 80 degrees Celsius; (3) Add the measured cyclohexanone and catalyst to IPDI while stirring, and then add the dried hollow ceramic microbeads in batches. After ultrasonic dispersion treatment for 35 minutes, pour the mixture into a mold, cure and shape the polyurethane prepolymer, and demold the mixture for later use.

[0031] Furthermore, in the polyurethane prepolymer synthesis preparation step, the catalyst in step (3) is isophorone diamine, which is used to accelerate the synthesis reaction of the polyurethane prepolymer and improve the reaction efficiency.

[0032] Furthermore, the tensile strength and elongation at break are tested according to ISO 527.2-2012 "Plastics - Determination of tensile properties Part 2: Test conditions for moulded and extruded plastics", and the Shore hardness is tested with reference to GB / T 2411-2008 "Plastics and hard rubber - Determination of indentation hardness (Shore hardness) using a durometer" standard.

[0033] Example 2 According to the material properties of different groups of polyurethane prepolymers in Example 1, the polyurethane prepolymer with the best comprehensive performance (Group 7) is selected as one of the raw materials. A method for preparing BMC plastics, calculated by weight: 70 parts of resin, 4 parts of pigment paste, 30 parts of polyurethane prepolymer, 12 parts of low shrinkage agent, 1 part of physical thickener, 50 parts of glass fiber, 6 parts of zinc stearate (Zn-ste), 0.6 parts of calcium hydroxide, 0.8 parts of curing agent, and 120 parts of kneading agent.

[0034] Furthermore, the resin is specifically 3501 resin, which is an unsaturated polyester resin.

[0035] Furthermore, the pigment paste includes unsaturated polyester resin and pigment powder, which is used to color the BMC material. The unsaturated polyester resin is obtained by condensation of unsaturated dibasic acid, saturated dibasic acid, diol, etc., and then dissolved in a cross-linking monomer. The pigment powder is selected from one or more of titanium dioxide, iron oxide pigment and anthraquinone pigment, and has good heat resistance, light resistance and chemical corrosion resistance.

[0036] Furthermore, the low shrinkage agent includes styrene and polystyrene, and the ratio of styrene to polystyrene is 1.8:1. The main function of the low shrinkage agent is to release internal stress through local relaxation and compensate for polymerization shrinkage, thereby achieving the effect of reducing shrinkage. In the preparation process of BMC composite materials, the addition of low shrinkage agents can effectively reduce the shrinkage deformation of products and improve the dimensional stability and surface quality of products; styrene can participate in the reaction as a cross-linking monomer, and can also inhibit the curing shrinkage of the resin through its thermal expansion. When polystyrene powder is used as a low shrinkage agent, its thermal expansion can be fully utilized to compensate for the curing shrinkage of the resin. After styrene and polystyrene are evenly mixed in a certain proportion, the shrinkage deformation of BMC composite materials can be effectively reduced, and the dimensional stability and surface quality of products can be improved.

[0037] Furthermore, the curing agent is tert-butyl ester, which has high reactivity and can quickly undergo cross-linking reaction with functional groups in the resin to form stable chemical bonds, thereby effectively promoting the curing of the resin. This efficient curing performance enables the BMC material to reach an ideal curing state in a shorter time, improving production efficiency. Tert-butyl ester curing agents also have certain advantages in environmental protection and safety. They usually do not contain toxic and harmful substances and have less harm to the environment and human health.

[0038] Furthermore, the kneading agent is calcium carbonate. The calcium carbonate powder has small particles and can be filled into the voids and pores in the BMC material, making the material more compact as a whole, reducing the generation of pores and defects, and helping to enhance the mechanical properties of the BMC material, such as tensile strength, compressive strength and hardness. Calcium carbonate is a common inorganic filler with a relatively low price, which can effectively reduce the cost of BMC materials, help improve product competitiveness, and expand market share. Calcium carbonate is a natural inorganic material, non-toxic and harmless, environmentally friendly, and reduces pollution and damage to the environment, which is in line with the concept of sustainable development.

[0039] Furthermore, the physical thickener is magnesium oxide, which rapidly increases the viscosity of the resin paste in the BMC material to ensure that the material maintains a stable consistency during processing. This efficient thickening performance helps to meet the BMC material's demand for rapid thickening, thereby improving production efficiency. In addition, the thickening effect of magnesium oxide is stable, which can ensure that the viscosity of each batch of BMC materials is consistent and reduce the production of defective products. As a common inorganic compound, magnesium oxide has a relatively low price. Using magnesium oxide as a thickener for BMC materials can effectively reduce production costs and improve the competitiveness of enterprises. The production process of magnesium oxide focuses on environmental protection and sustainability, which meets the green production requirements of modern society. As a thickener for BMC materials, it not only improves the performance of the material, but also reduces the impact on the environment. In addition, magnesium oxide can also be recycled, further reducing resource waste and environmental pollution.

[0040] Furthermore, the glass fiber is chopped glass fiber. The chopped glass fiber is easier to mix evenly with other components such as resin and filler during the mixing process to form a stable mixture, which helps to ensure that the BMC material has consistent physical and chemical properties during the molding process. Although long glass fibers can theoretically provide higher strength, during the preparation and molding of BMC materials, long glass fibers are easily broken and bent, resulting in a decrease in average length, which in turn affects the strength of the product; in contrast, chopped glass fibers can better maintain their shape and length during the mixing and molding process, thereby more effectively improving the strength of BMC products. The addition of chopped glass fibers can also improve the toughness of the BMC material, enabling it to better absorb and disperse energy when subjected to external forces, thereby improving the impact resistance and durability of the product.

[0041] Furthermore, the raw materials of the polyurethane prepolymer used in this embodiment are as follows: IPDI and hollow ceramic microspheres are recorded in parts by weight, 60 parts of IPDI and 40 parts of hollow ceramic microspheres.

[0042] Furthermore, the curing conditions of the polyurethane prepolymer are room temperature curing for 14 days and then curing at 100 degrees Celsius for 24 hours.

[0043] Further, a BMC plastic preparation process comprises the following specific steps: S1. Incoming inspection to ensure the quality of raw materials, maintain production order, and guarantee the final quality of products. Glass fiber needs to undergo iron inspection; S2. Storage of raw materials: Raw materials should be stored in a ventilated and dry place at room temperature. Appropriate storage conditions can maintain the stability and performance of raw materials and prevent them from chemical reactions or physical changes. It should be noted that tert-butyl ester curing agent is a dangerous organic peroxide. Fire and heat sources should be avoided during storage and transportation to prevent explosions and other dangerous accidents. S3. Weigh, check and clean the surface of the electronic scale tray, weigh the raw materials of corresponding weight fractions, use a foam bowl to weigh polyester resin and pigment powder, use a measuring cup and a plastic box to weigh curing agent, zinc stearate, and calcium hydroxide, and clean the electronic scale and the work site after weighing; S4, pigment paste preparation, a. Place the weighed polyester resin and pigment powder in a barrel; b. Check and clean the mixer blades, place the prepared pigment at the working position, put in the mixer blades and start stirring. During the stirring process, the pigment and polyester resin on the side of the barrel need to be scraped into the pigment paste to keep the side of the barrel free of residue; continue stirring until the color is evenly mixed. After stirring, clean the blades and take out the barrel for standby use; c. Check and clean the roller of the grinder, then turn on the grinder, use a scoop to add material to the pressure roller, add an appropriate amount each time, and add again when there is less material on the pressure roller. After all is completed, use a scraper fineness meter to check the fineness of the pigment paste. The scraper fineness requirement is ≤25. If it meets the standard, the grinding is completed. If it does not meet the standard, it needs to be ground again until it meets the requirements. The ground pigment paste is barreled, then shut down, and the grinder and production site are cleaned; S5. Preparation of low shrinkage agent: a. After checking that there are no abnormalities in the mixing barrel and equipment, use a copper wrench to open the styrene barrel, and then insert the suction pump. When the machine propeller is stationary, draw in styrene through the pump, and add styrene at one time according to the ratio. Pay attention to pumping out the barrel cleanly; b. Start the propeller, add polystyrene while the propeller is working. After the addition is completed, start the timer to start timing. After stirring for 150 minutes, the equipment automatically stops. At this time, the low shrinkage agent is a milky white viscous liquid without polystyrene particles; c. Put the stirred low shrinkage agent into a 14-mesh filter screen through a pipe, and then flow it into the iron barrel. Use a copper wrench to lock the lid, and mark the date, barrel number and serial number as shown in the figure above, clean the mesh screen for later use; S6, kneading, a. Check and clean the inside of the kneading machine; b. First add unsaturated resin, pigment paste, low shrinkage agent, curing agent, zinc stearate, calcium hydroxide, stir for 1.5 minutes, pay attention to the unsaturated resin and low shrinkage agent should be drained from the barrel; c. Turn on the kneading machine, stir for 1 minute, then add calcium carbonate and aluminum hydroxide according to the proportion, then close the cylinder cover, start kneading and timing; d. After stirring for 10 minutes, observe the kneading uniformity, there should be no separation between the resin and the filler, and the filler is completely soaked in the resin (during the kneading process, it is necessary to stop once, use a scraper to clean the resin and powdery material on the side of the cylinder, and keep the cylinder side No residue), then start to add glass fiber evenly and slowly for multiple times, and stir for 8 minutes, 13 minutes, and 15 minutes after adding; (glass fiber poured too quickly: it is easy to cause uneven mixing; poured too slowly: it is easy to cause fiber bundle damage); e. After self-inspection, the appearance of the material is normal, start discharging and put it into an airtight film packaging bag. The appearance of the material is white glass fiber or powder without visible to the naked eye, and there is no foreign impurity; f. Put a label on the packaging bag, and after the production is completed, clean the raw materials in the cylinder and the production site; g. The packaged BMC material is naturally matured at room temperature for 5 days. This process helps to further integrate and evenly distribute the components in the material, and improve the performance and stability of the material; h. After the aging is completed, the BMC material is added to the preheated mold for pressing and molding. During the pressing process, it is necessary to control the appropriate pressure, temperature and time to ensure that the material can fully fill the mold and solidify. After pressing and molding, take out the solidified BMC product, trim and polish it to make its surface smooth. Then, quality inspection is carried out to obtain the finished product; S7. Packaging: Cut the nylon rope, arrange the inner bag, use the nylon rope to tie the bag mouth, pay attention to tying the slipknot, and place the packed and tied finished products on the pallet. There are no more than 15 bags per pallet. Be careful not to place them beyond the pallet to prevent them from being damaged during loading or transportation. S8. Flattening. Check and clean foreign objects on the work surface of the hydraulic press. Set the stroke height of the hydraulic press. Place the raw materials on the work surface. Start the equipment for flattening. After flattening, take out the materials and place them on a pallet. If you hear a cracking sound during the flattening process, check the inner and outer bags of the packaging and replace them immediately or put on another bag. When placing the pallet, stack up to 4 layers and do not let the materials exceed the edge of the pallet to prevent damage during loading or transportation. Turn off the hydraulic press and clean the equipment and production site.

[0044] Furthermore, in the BMC plastic preparation process, dust masks and protective gloves need to be worn throughout steps S1-S8, and fireworks are prohibited in steps S4, S5, and S6.

[0045] Furthermore, in the BMC plastic preparation process, in step S6 d, after adding the glass fiber, the stirring time is 13 minutes.

[0046] Furthermore, in the BMC plastic preparation process, in step S6h, different pressing times are adopted according to the difference in mold size, as shown in Table 2: Table 2 Pressing time corresponding to different molds Example 3 Compared with Example 2, the only difference in Example 3 is that the formula of the BMC plastic is different: Resin 60 parts, pigment paste 4 parts, polyurethane prepolymer 40 parts, low shrinkage agent 12 parts, physical thickener 1 part, glass fiber 50 parts, zinc stearate (Zn-ste) 6 parts, calcium hydroxide 0.6 parts, curing agent 0.8 parts, kneading agent 120 parts.

[0047] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0048] Example 4 Compared with Example 2, the only difference in Example 4 is that the formula of the BMC plastic is different: 80 parts of resin, 4 parts of pigment paste, 20 parts of polyurethane prepolymer, 12 parts of low shrinkage agent, 1 part of physical thickener, 50 parts of glass fiber, 6 parts of zinc stearate (Zn-ste), 0.6 parts of calcium hydroxide, 0.8 parts of curing agent, and 120 parts of kneading agent.

[0049] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0050] Example 5 Compared with Example 2, the only difference in Example 5 is that the formula of the BMC plastic is different: 90 parts of resin, 4 parts of pigment paste, 10 parts of polyurethane prepolymer, 12 parts of low shrinkage agent, 1 part of physical thickener, 50 parts of glass fiber, 6 parts of zinc stearate (Zn-ste), 0.6 parts of calcium hydroxide, 0.8 parts of curing agent, and 120 parts of kneading agent.

[0051] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0052] Example 6 Compared with Example 2, the only difference in Example 6 is that the formula of the BMC plastic is different: 70 parts of resin, 4 parts of pigment paste, 30 parts of polyurethane prepolymer, 12 parts of low shrinkage agent, 1 part of physical thickener, 50 parts of glass fiber, 6 parts of zinc stearate (Zn-ste), 0.6 parts of calcium hydroxide, 0.3 parts of curing agent, and 120 parts of kneading agent.

[0053] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0054] Example 7 Compared with Example 2, the only difference in Example 7 is that the formula of the BMC plastic is different: 70 parts of resin, 4 parts of pigment paste, 30 parts of polyurethane prepolymer, 12 parts of low shrinkage agent, 1 part of physical thickener, 50 parts of glass fiber, 6 parts of zinc stearate (Zn-ste), 0.6 parts of calcium hydroxide, 1 part of curing agent, and 120 parts of kneading agent.

[0055] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0056] Example 8 Compared with Example 2, the only difference in Example 8 is that the preparation process of BMC plastic is different: In step S6 d, after adding the glass fiber, the stirring time is 8 minutes.

[0057] The preparation formula and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0058] Example 9 Compared with Example 2, the only difference in Example 9 is that the preparation process of BMC plastic is different: In step S6 d, after adding the glass fiber, the stirring time is 15 minutes.

[0059] The preparation formula and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0060] Comparative Example 1 Compared with Example 2, the only difference in Comparative Example 1 is that the formula of the BMC plastic is different: 70 parts of resin, 4 parts of pigment paste, 30 parts of polyurethane prepolymer, 12 parts of low shrinkage agent, 1 part of physical thickener, 50 parts of glass fiber, 6 parts of zinc stearate (Zn-ste), 0.6 parts of calcium hydroxide, 0.1 parts of curing agent, and 120 parts of kneading agent.

[0061] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0062] Comparative Example 2 Compared with Example 2, the only difference in Comparative Example 2 is that the formula of BMC plastic is different: 50 parts of resin, 4 parts of pigment paste, 50 parts of polyurethane prepolymer, 12 parts of low shrinkage agent, 1 part of physical thickener, 50 parts of glass fiber, 6 parts of zinc stearate (Zn-ste), 0.6 parts of calcium hydroxide, 0.8 parts of curing agent, and 120 parts of kneading agent.

[0063] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0064] Comparative Example 3 Compared with Example 2, the only difference in Comparative Example 3 is that the formula of BMC plastic is different: 100 parts of resin, 4 parts of pigment paste, 0 parts of polyurethane prepolymer, 12 parts of low shrinkage agent, 1 part of physical thickener, 50 parts of glass fiber, 6 parts of zinc stearate (Zn-ste), 0.6 parts of calcium hydroxide, 0.8 parts of curing agent, and 120 parts of kneading agent.

[0065] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0066] Comparative Example 4 Compared with Example 2, the only difference in Comparative Example 4 is that the formula of the BMC plastic is different: Resin 70 parts, pigment paste 4 parts, polyurethane prepolymer 30 parts, low shrinkage agent 12 parts, physical thickener 1 part, glass fiber 50 parts, zinc stearate (Zn-ste) 6 parts, calcium hydroxide 0.6 parts, curing agent 0 parts, kneading agent 120 parts.

[0067] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0068] Comparative Example 5 Compared with Example 2, the only difference in Comparative Example 4 is that the formula of the BMC plastic is different: Resin 70 parts, pigment paste 4 parts, polyurethane prepolymer 30 parts, low shrinkage agent 12 parts, physical thickener 1 part, glass fiber 50 parts, zinc stearate (Zn-ste) 6 parts, calcium hydroxide 0.6 parts, curing agent 0.8 parts, kneading agent 80 parts.

[0069] Comparative Example 6 Compared with Example 2, the only difference in Comparative Example 4 is that the formula of the BMC plastic is different: 100 parts of resin, 4 parts of pigment paste, 0 parts of polyurethane prepolymer, 12 parts of low shrinkage agent, 1 part of physical thickener, 50 parts of glass fiber, 6 parts of zinc stearate (Zn-ste), 0.6 parts of calcium hydroxide, 0 parts of curing agent, and 120 parts of kneading agent.

[0070] The preparation process and other relevant parameters of this embodiment are consistent with those of embodiment 2.

[0071] Table 3 Physical and electrical properties of BMC plastics Note: Density test is carried out according to GB / T 1033.1-2008, tensile strength, flexural strength and impact strength are tested according to ISO 527.2-2012 "Plastics - Determination of tensile properties Part 2: Test conditions for moulding and extruded plastics", and volume resistivity test is carried out according to GB / T 1410-2006.

[0072] Combined with the data of Examples 2 to 5, Comparative Examples 2 and 3, it is shown that with the increase in the amount of polyurethane prepolymer added, the density of the BMC plastic shows a downward trend, the tensile strength, flexural strength and impact strength of the BMC plastic show a trend of first increasing and then decreasing, and the volume resistivity of the BMC plastic shows an upward trend; when the amount of polyurethane prepolymer added is 10-30 parts, although the density of the BMC plastic decreases, the decrease is small. When the polyurethane prepolymer is continued to be added and the amount added reaches 40 parts, the density of the BMC plastic decreases significantly compared with the addition of 30 parts of the polyurethane prepolymer. The tensile strength and flexural strength of the BMC plastic show that the values ​​are the highest when the amount of polyurethane prepolymer added is 10 parts, but are lower than the tensile strength when the amount of polyurethane prepolymer added is 20 parts and 30 parts. Compared with the strength and bending strength, the difference is very small. Compared with the case without adding polyurethane prepolymer, the impact strength of BMC plastic increases. The impact strength value of BMC plastic shows that the value is the highest when the addition amount of polyurethane prepolymer is 30 parts. When the addition amount of polyurethane prepolymer is 50 parts or no polyurethane prepolymer is added, compared with the addition amount of polyurethane prepolymer is 10-30 parts, the tensile strength and bending strength of BMC plastic decrease significantly. When the addition amount of polyurethane prepolymer is 20-50 parts, the volume resistivity of BMC plastic increases significantly. When the addition amount of polyurethane prepolymer is 10 parts, compared with the case without adding polyurethane prepolymer, the volume resistivity of BMC plastic is still greatly improved. It can be seen that polyurethane prepolymer has a significant promoting effect on the increase of volume resistivity of BMC plastic.

[0073] Combining the data of Example 2, Example 6, Example 7, Comparative Example 1 and Comparative Example 4, it is shown that the curing agent has a small effect on the density of the BMC plastic, the density of the BMC plastic is proportional to the amount of curing agent added, has a small effect on the tensile strength and bending strength of the BMC plastic, and has almost no effect on the impact strength and volume resistivity of the BMC plastic.

[0074] Combined with the data of Example 2, Example 8 and Example 9, it is shown that in the kneading process of the preparation process, the stirring time after adding the glass fiber has almost no effect on the density of the BMC plastic. If the stirring time is too long or too short after adding the glass fiber, the tensile strength, flexural strength, impact strength and volume resistivity of the BMC plastic will be reduced. If the stirring time is too short, the reduction in the tensile strength, flexural strength, impact strength and volume resistivity of the BMC plastic will be greater.

[0075] Combined with the data of Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 6, when only the curing agent is added, the physical properties of the BMC plastic are less affected, and when only the polyurethane prepolymer is added, the physical and electrical properties of the BMC plastic are greatly affected. When the curing agent and the polyurethane prepolymer are added together, the physical and electrical properties of the BMC plastic are more affected.

[0076] Figure 2 It shows that with the increase of the amount of kneading agent added, the water absorption rate of BMC plastic gradually decreases. After the amount of kneading agent added reaches 120 parts, the water absorption rate of BMC plastic almost no longer changes. At this time, the water absorption rate of BMC plastic is 0.2%-0.3% lower than the industry average, which means that in a humid environment, the material can maintain good performance stability and is not prone to physical performance degradation due to water absorption. At the same time, the data of Example 2 and Comparative Example 5 in Table 3 show that the reduction in the amount of kneading agent added leads to a slight decrease in the physical and electrical properties of BMC plastic.

[0077] Figure 3 It shows that although the addition of polyurethane prepolymer increases the physical and electrical properties of BMC plastics, the curing time is prolonged. After adding curing agent, the curing time of BMC plastics is greatly reduced. When the curing agent addition fraction is 0.3-1.0 parts, the curing time of BMC plastics tends to be normal. Figure 4 It shows that ceramic microspheres are compatible with BMC plastics.

Claims

1. A method for preparing BMC plastic, characterized in that: The formula is calculated by weight, and its raw materials include the following components: 60-90 parts of resin, 1-6 parts of pigment paste, 10-40 parts of polyurethane prepolymer, 8-18 parts of low shrinkage agent, 0.8-1.4 parts of physical thickener, 40-65 parts of glass fiber, 3-7 parts of zinc stearate (Zn-ste), 0.4-1 parts of calcium hydroxide, 0.3-1 parts of curing agent, and 100-140 parts of kneading agent.

2. A method for preparing BMC plastic according to claim 1, characterized in that: The polyurethane prepolymer comprises IPDI and hollow ceramic microspheres.

3. A method for preparing BMC plastic according to claim 2, characterized in that: The polyurethane prepolymer is synthesized according to the following steps: A. Inorganic material treatment: prepare a solution with anhydrous ethanol and distilled water in a ratio of 8:2, add 1-5% silane coupling agent to the solution, mix well, pour into a beaker containing pre-dried hollow ceramic microbeads, put into an ultrasonic stirrer at a water temperature of 50-60 degrees Celsius, and treat for 50-60 minutes; B. Use a circulating water vacuum pump to filter out most of the filtrate from the treated hollow ceramic microbeads, and then put them into an oven to dry for 6-8 hours. The oven temperature is 75-90 degrees Celsius. C. Add the measured cyclohexanone into IPDI while stirring, and then add the dried hollow ceramic microbeads in batches for multiple times. After ultrasonic dispersion treatment for 30-40 minutes, pour into the mold, cure under certain conditions to obtain a polyurethane prepolymer, and demold for standby use.

4. A method for preparing BMC plastic according to claim 3, wherein the certain conditions in step B are curing at room temperature for 14 days and then curing at 80-120 degrees Celsius for 24 hours.

5. A method for preparing BMC plastic according to claim 4, characterized in that: The components of the polyurethane prepolymer, IPDI and hollow ceramic microspheres are as follows, by weight: 50-80 parts of IPDI and 20-50 parts of hollow ceramic microspheres.

6. A BMC plastic preparation process, using a BMC plastic preparation method according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Incoming inspection to ensure the quality of raw materials, maintain production order, and guarantee the final quality of products; S2. Raw material storage: Raw materials should be stored in a ventilated and dry place at room temperature; S3, weighing, weighing the raw materials of corresponding weight fractions, wherein a foam bowl is used to weigh the polyester resin and pigment powder, and a measuring cup and a plastic box are used to weigh the curing agent, zinc stearate and calcium hydroxide; S4, pigment paste preparation, a. weigh the unsaturated polyester resin and pigment powder, place them in a bucket; b. check and clean the mixer blades, place the prepared pigment in the working position, put in the mixer blades and start stirring until the color is evenly mixed, clean the blades, take out the barrel for later use; c. check and clean the grinding machine roller, then turn on the grinder, and use a scraper fineness meter to check the fineness of the pigment paste until it meets the requirements, and then put the ground pigment paste into a bucket; S5. Preparation of low shrinkage agent: a. Check the mixing barrel and equipment, use a copper wrench to open the styrene barrel, and add styrene at one time according to the ratio; b. Start the propeller, add polystyrene, start the timer, stir for 130-170 minutes, and the equipment stops automatically; c. Put the stirred low shrinkage agent into the filter screen through the pipe, and then flow into the iron barrel, and lock the lid with a copper wrench; S6, kneading, a. Check and clean the inside of the kneading machine; b. First add pigment paste, low shrinkage agent, curing agent, zinc stearate, calcium hydroxide, and stir for 1-2 minutes; c. Turn on the kneading machine, stir for 1-2 minutes, then add calcium carbonate or aluminum hydroxide according to proportion, then close the cylinder cover, start kneading and timing; d. After stirring for 10 minutes, observe the kneading uniformity, then start to add glass fiber uniformly and slowly for multiple times, and stir again after adding; e. After self-inspection, if there is no abnormality in the appearance of the material, start discharging and put it into an airtight film packaging bag; f. Attach labels to the packaging nylon bags and inner bags; g. Naturally mature the packaged BMC materials at room temperature for 5 days; h. After the aging is completed, the BMC material is added into the preheated mold, pressed and formed, and quality inspected to obtain the finished product; S7, packaging, cutting nylon ropes, arranging inner bags, and placing the packaged and tied finished products on pallets; S8, flattening, check and clean foreign objects on the work surface of the hydraulic press, set the stroke height of the hydraulic press, place the product on the work surface, and start the equipment for flattening.

7. A BMC plastic preparation process according to claim 6, characterized in that: In step S6 d, after adding the glass fiber, the stirring time is 8-15 minutes.

Citation Information

Patent Citations

  • Low-density bulk molding compound (BMC) and preparation method thereof

    CN103525115A

  • Toughening low-shrinkage lump molding material and preparation method thereof

    CN108676339A

  • Air-permeable foam and preparation method therefor

    WO2024239675A1